Evaluation of the tumor registration error in biopsy procedures performed under real‐time PET/CT guidance. Issue 10 (12th July 2017) - Fanchon, Louise M.; Apte, Adytia; Schmidtlein, C. Ross; Yorke, Ellen; Hu, Yu‐Chi; Dogan, Snjezana; Hatt, Mathieu; Visvikis, Dimitris; Humm, John L.; Solomon, Stephen B.; Kirov, Assen S.
Abstract : Purpose: The purpose of this study is to quantify tumor displacement during real‐time PET/CT guided biopsy and to investigate correlations between tumor displacement and false‐negative results. Methods: 19 patients who underwent real‐time 18 F‐FDG PET‐guided biopsy and were found positive for malignancy were included in this study under IRB approval. PET/CT images were acquired for all patients within minutes prior to biopsy to visualize the FDG‐avid region and plan the needle insertion. The biopsy needle was inserted and a post‐insertion CT scan was acquired. The two CT scans acquired before and after needle insertion were registered using a deformable image registration (DIR) algorithm. The DIR deformation vector field (DVF) was used to calculate the mean displacement between the pre‐insertion and post‐insertion CT scans for a region around the tip of the biopsy needle. For 12 patients one biopsy core from each was tracked during histopathological testing to investigate correlations of the mean displacement between the two CT scans and false‐negative or true‐positive biopsy results. For 11 patients, two PET scans were acquired; one at the beginning of the procedure, pre‐needle insertion, and an additional one with the needle in place. The pre‐insertion PET scan was corrected for intraprocedural motion by applying the DVF. The corrected PET was compared with the post‐needle insertion PET to validate the correction method. Results: The mean displacement of tissue around the needle between the pre‐biopsy CT and the postneedle insertion CT was 5.1 mm (min = 1.1 mm, max = 10.9 mm and SD = 3.0 mm). For mean displacements larger than 7.2 mm, the biopsy cores gave false‐negative results. Correcting pre‐biopsy PET using the DVF improved the PET/CT registration in 8 of 11 cases. Conclusions: The DVF obtained from DIR of the CT scans can be used for evaluation and correction of the error in needle placement with respect to the FDG‐avid area. Misregistration between the pre‐biopsy PET and the CT acquired with the needle in place was shown to correlate with false negative biopsy results.